Transdifferentiation: a cell and molecular reprogramming process - Sisakhtnezhad, Sajjad; Matin, Maryam M (Cell and tissue research, 2012)
Evidence has emerged recently indicating that differentiation is not entirely a one-way process, and that it is possible to convert one cell type to another, both in vitro and in vivo. This phenomenon is called transdifferentiation, and is generally defined as the stable switch of one cell type to another. Transdifferentiation plays critical roles during development and in regeneration pathways in nature. Although this phenomenon occurs rarely in nature, recent studies have been focused on transdifferentiation and the reprogramming ability of cells to produce specific cells with new phenotypes for use in cell therapy and regenerative medicine. Thus, understanding the principles and the mechanism of this process is important for producing desired cell types. Here some well-documented examples of transdifferentiation, and their significance in development and regeneration are reviewed. In addition, transdifferentiation pathways are considered and their potential molecular mechanisms, especially the role of master switch genes, are considered. Finally, the significance of transdifferentiation in regenerative medicine is discussed.